VALIDATION OF WARFARIN ANALYSIS METHOD IN HUMAN BLOOD PLASMA USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY WITH FLUORESCENCE DETECTION - PUTRIANA, NORISCA ALIZA; RUSDIANA, TAOFIK; ROSTINAWATI, TINA; AKBAR, MOHAMMAD RIZKI; NURFUADAH, ILMA (International Journal of Applied Pharmaceutics, 2022)
Objective: Validation of analysis method is important, especially in analyzing narrow-index drugs such as warfarin (WF). This study aimed to obtain a validated method of analyzing warfarin in human plasma according to European Medicine Agency guidelines. Methods: The optimum conditions for the analysis of warfarin in human plasma using fluorescence detector HPLC with Chiralcel OD-RH column (4.6 x 150 mm i.d., 5μm); Chiralcel OD-RH guard column (4.0 x 10 mm, 5μm), column temperature 45 °C. The mobile phase used was acetonitrile: phosphate buffer pH 2 (40:60), with an isocratic flow rate of 1 ml/min and an injection volume of 20 μl. Excitation and emission wavelengths were 310 and 350 nm (warfarin) and 300 and 400 nm (griseofulvin). The retention time of griseofulvin was 6-7.5 min; R-warfarin was 10-11.5 min; S-warfarin was 14-16 min. Results: The result of this validation obtained the optimum condition. This method yielded LOD values of 0.0674 ppm (R-warfarin) and 0.0897 ppm (S-warfarin). LOQ values were 0.225 ppm (R-warfarin) and 0.298 ppm (S-warfarin). Linearity at concentrations of 0.2-3 ppm with the line equation y = 0.0705x+0.0704 with R2 = 0.978 for R-warfarin and y = 0.0513x+0.0297 with R² = 0.9924 for S-warfarin. 75% of the seven concentrations met the reverse concentration requirements, which were below±15%. This method met the requirements of accuracy and precision within and between runs, selectivity and carryover where the %RSD and %diff values were below±15% Conclusion: This analytical method can be declared valid and can be used for sample measurement in warfarin pharmacokinetic studies.